Pengelolaan Arsip Personal Berbasis Digital Dengan Pendekatan Records Continuum Model Di IAIN Curup - Histori, Oktafian; Anggraini, Yeti Tamala (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2025)
This study aims to determine how personal archives are managed at IAIN Curup including the challenges and practices implemented. This study also aims to determine the role of archivists in the personal archive management system, and analyze the stages of digital-based personal archive management with the records continuum model (RCM) approach at IAIN Curup. This study uses a descriptive qualitative research method. Data collection techniques with observation, interviews and documentation. Data analysis techniques in this study by reducing data, presenting data and drawing conclusions according to research needs as results and discussions. The results of the study indicate that personal archive management at IAIN Curup is still very dependent on manual systems, is in the early stages of digitalization with challenges in infrastructure and management. The results of the study also show that archivists at IAIN Curup have a major role in managing institutional archives. Personal archive management carried out by archivists is related to institutional archives which are also personal documents or archives. Personal archive management with the records continuum model approach at IAIN Curup is expected to optimize digital archive management so that it can support operations and administration more efficiently in the future. Staff competency enhancement, technological infrastructure development, and information system integration are important steps to achieve more efficient and sustainable archive management.